Menelusuri kebenaran letusan Gunung Merapi 1006 - Supriati Dwi Andreastuti; Chris Newhall; Joko Dwiyanto (Indonesian Journal on Geoscience, 2006)
http://dx.doi.org/10.17014/ijog.vol1no4.20064Until now, the large eruption of Merapi in 1006 is believed to take place although the truth is still debatable. Previous investigation proposed that the ”pralaya” of the Ancient Mataram Kingdom in 928 Saka (1006) was due to a volcanic activity. Bemmelen also inferred that impact of the eruption had destroyed and covered the Mendut and Borobudur Temples and dammed the Progo River. However, if the “pralaya” was caused by Merapi eruption, why the deposit that correlates to the the eruption is not recognized. If so, the eruption that covered the temples should have been very large, and left deposits around Merapi and of course easy to find. Historically, the “pralaya“ mentioned in the Pucangan Inscription did not happen in 1006, but in 1016 or 1017. However the “pralaya“ was caused by the attack of King Wurawari, not by the Merapi eruption. According to the history of Merapi eruptions, 11 large eruptions have occurred since 3000 years ago. However, none of those fi t with 1006 eruption. Except the large eruption (VEI 3-4), that produced Selo tephra, dated 1112 ± 73 years BP (765-911).